PENGARUH PENGUASAAN KALOR TERHADAP HASIL BELAJAR FISIKA PADA MATERI POKOK GELOMBANG ELEKTRO MAGNATIK DI KELAS X SMA NEGERI 1 PADANG BOLAK JULU - Dedes Asriani Asriani Siregar (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2024)
The aim of this research was to know whether there was any significant influence of heat mastery and physic achievement in electromagnetic wave subject at the tenth grade students of SMA Negeri 1 Padang Bolak Julu. The method of this research was descriptive. By using total sampling technique, the writer took 70 students as the sample. Based on descriptive analysis, the average of heat mastery was 73, it was categorized “good” and the average of electromagnetic wave was 76.5, it was categorized “good”.Based statistic inferential analysis by using ttest to test hypothesis, it could be gotten tcount = 5.71 and ttable = 1.66 at error level 5%. It could be seen tcount was greater than ttable (5.78 >1.66). It means alternative hypothesis was accepted. In the other words, there was any significant influence of heat mastery and physic achievement in electromagnetic wave subject at the tenth grade students of SMA Negeri 1 Padang Bolak Julu.